Radiation modification of the structure of layer crystals of sulfide gallium - Madatov, R.S.; Gadzhieva, N.N.; Asadov, F.G.; Asadova, Z.I. (Вопросы атомной науки и техники, 2018)
he radiation modification of the structure of a layered GaS crystal by the Fourier-IR and Raman spectroscopy methods in the absorbed dose (Фγ = 30…200 krad) of gamma-irradiation was studied. It was established that at irradiation doses of Фγ ≤ 50 krad a half-width and intensities Raman lines and IR adsorption bands the characterizing the layer oscillations does not change, which is due to the stability of the crystal lattice. At absorbed doses of Фγ ≥ 50 krad, changes in these parameters are observed, which lead to a change in the degree of structural disorder and, consequently, of the radiation structural modification of the layered crystal. Fourier-IR reflection spectra revealed that gamma-irradiation at doses of Фγ ≥ 50 krad leads to a deterioration of the surface state of gallium sulphide. Досліджена радіаційна модифікація структури шаруватого кристала GaS методом фур'є-раманспектроскопії в області поглиненої дози гамма-опромінення (Фγ = 30...200 крад). Встановлено, що при дозах опроміненні Фγ ≤ 50 крад напівширина і інтенсивності раман-ліній, що характеризують шарові коливання, не змінюються, що пов'язано зі стабільністю кристалічної решітки. При поглинених дозах Фγ ≥ 50 крад спостерігаються зміни цих параметрів, що викликано зміною ступеня структурного безладу і, отже, радіаційною структурною модифікацією шаруватого кристала. За фур'є-ІЧ-спектрами відображення виявлено, що гамма-опромінення при дозах Фγ ≥ 50 крад призводить до погіршення поверхневого стану сульфіду галію. Исследована радиационная модификация структуры слоистого кристалла GaS методом фурье-раманспектроскопии в области поглощенной дозы гамма-облучения (Фγ = 30…200 крад). Установлено, что при дозах облучении Фγ ≤ 50 крад полуширина и интенсивности раман-линий, характеризующие слоевые колебания, не изменяются, что связано со стабильностью кристаллической решетки. При поглощенных дозах Фγ ≥ 50 крад наблюдаются изменения этих параметров, что вызвано изменением степени структурного беспорядка и, следовательно, радиационной структурной модификацией слоистого кристалла. По фурье-ИКспектрам отражения выявлено, что гамма-облучение при дозах Фγ ≥ 50 крад приводит к ухудшению поверхностного состояния сульфида галлия.